Assessment and Accountability to Support Meaningful Learning - Scott Marion; Paul Leather (Arizona State University, 2015)
This paper presents an overview of New Hampshire's efforts to implement a pilot accountability system designed to support deeper learning for students and powerful organization change for schools and districts. The accountability pilot, referred to as Performance Assessment of Competency Education or PACE, is grounded in a competency- based educational approach designed to ensure that students have meaningful opportunities to achieve critical knowledge and skills. These opportunities are judged by the outcomes students achieve and not by inputs such as seat time. Therefore, students must achieve these competencies before moving on to the next major learning targets and/or graduating from high school. High quality performance assessments play a crucial role in the PACE system because of the need to have assessments that measure the depths of student understanding of these complex learning targets. Performance assessments are used as both summative and interim measures in the PACE system as a way to document student learning of the competencies and to support remediation or extension interventions. The paper describes the system of assessments being implemented as part of the PACE pilot as well as providing a discussion of the technical quality issues the state is working to address as part of this accountability pilot. For example, being able to produce valid and comparable annual determinations for all students each year is a considerable technical challenge as well as documenting the degree to which all students are held to the same threshold expectations (equity). The paper concludes by relating the PACE initiative to the push for deeper and more meaningful learning for students.